2020
DOI: 10.1097/md.0000000000021303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depth of anesthesia on the phase lag entropy in patients undergoing general anesthesia by propofol

Abstract: The PLEM100 (Inbody Co., Ltd., Seoul, Korea) is a device for measuring phase lag entropy (PLE), a recently developed index for the quantification of consciousness during sedation and general anesthesia. In the present study, we assessed changes in PLE along with the level of consciousness during the induction of general anesthesia using propofol. PLE was compared with the bispectral index (BIS), which is currently the most commonly used index of consciousness. After obtaining Institutional Review Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Each EEG monitors have their own algorithms to calculate the index for the target of general anesthesia [23]. For example, 40-60 of BIS, 25-50 of PSI, and 40-60 of PLE is a range of index for adequate general anesthesia [11,23]. Phase lag entropy also showed high prediction probability in our study.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Each EEG monitors have their own algorithms to calculate the index for the target of general anesthesia [23]. For example, 40-60 of BIS, 25-50 of PSI, and 40-60 of PLE is a range of index for adequate general anesthesia [11,23]. Phase lag entropy also showed high prediction probability in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Similar neural circuit mechanisms are involved, as evident by the similar EEG dynamics induced by sevoflurane and propofol [4]. Looking for common EEG features, propofol and sevoflurane anesthesia were depicted by alpha (8)(9)(10)(11)(12) and slow (<1 Hz) oscillations [4]. The EEG features of sevoflurane were discriminable from that of propofol because of increased power and coherence in the theta wave (4-7 Hz) [4].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, theoretically, the PLE score could be less affected by EEG than the BIS; however, there have been few studies on the relationship between the PLE score and PLE-EMG. Although several studies showed PLE score has correlation with BIS for evaluating consciousness and depth of anesthesia during general anesthesia (11,12,24), the present study is meaningful since it is the first to investigate the PLE-EMG effect on the PLE score.…”
Section: Discussionmentioning
confidence: 85%
“…A previous study reported no changes in the BIS score even after 10 min of sugammadex reversal (22); however, the EMG activity was a single entity rather than dividing it into low and high groups, which may differ from other studies. The PLE monitor has been recently approved for clinical use, with several studies assessing its usefulness and comparison with the BIS; moreover, it has been shown as useful for LOC evaluation in general anesthesia (11,12,23,24). PLE employs EEG signals with ranges of 0.1-1 and 32-45 Hz while PLE-EMG uses signals >45 Hz.…”
Section: Discussionmentioning
confidence: 99%